Review of the Influence of Teacher Motivation on the Use of Interactive Whiteboards - Rojas Segovia, Miriam M. (2019)
The present article is a topic´s revision and it pretends to give a general vision of the recollected data about the use of interactive digital boards in the sessions of teaching-learning process´ development that takes as a determinant factor the teacher´s motivation. It has been made an examination of the available literature online to elaborate an analysis of the actual situation of this innovating didactic tool and its relation with the teacher´s predisposition, as part of the final project for the Academic Investigation subject in the Technological University of Peru. After the investigation, it concluded, until the edition’s date, there are no enough researches that center their attention in the teacher´s attitude, especially in Peru, so it can´t be determined if there is a direct relation between these aspects and it´s recommended to develop projects that gives relevance to the educator in the efficient use of the technology with the purpose of achieve a qualified education that is adapted to the emergent information society´s standards.